Characterization of Nanomaterials: Selected Papers from 6th Dresden Nanoanalysis Symposiumc - Zschech, Ehrenfried; Sinclair, Robert; Martins, Rodrigo; Sebastiani, Marco; Sartori, Sabrina (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue "Characterization of Nanomaterials" collects nine selected papers presented at the 6th Dresden Nanoanalysis Symposium, held at Fraunhofer Institute for Ceramic Technologies and Systems in Dresden, Germany, on 31 August 2018. Following the specific motto of this annual symposium "Materials challenges-Micro- and nanoscale characterization", it covered various topics of nanoscale materials characterization along the whole value and innovation chain, from fundamental research up to industrial applications. The scope of this Special Issue is to provide an overview of the current status, recent developments and research activities in the field of nanoscale materials characterization, with a particular emphasis on future scenarios. Primarily, analytical techniques for the characterization of thin films and nanostructures are discussed, including modeling and simulation. We anticipate that this Special Issue will be accessible to a wide audience, as it explores not only methodical aspects of nanoscale materials characterization, but also materials synthesis, fabrication of devices and applications.